Adubação nitrogenada de cobertura no feijoeiro de invernoprimavera em três sistemas de cultivo - Fiorentin, Ciro Franco [UNESP]; Lemos, Leandro Borges [UNESP]; Jardim, Celso Antonio [UNESP]; Fornasieri Filho, Domingos [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The aim of this study was to evaluate the nitrogen topdressing influence in common bean irrigated (winter-spring), in the first year of no tillage implementation. The experimental design was split-plot with three replications in randomized blocks. The plots were formed by three types of ground cover, corn-grain, corn-grain intercropped with Brachiaria ruziziensis and only B. ruziziensis. The subplots were formed by five doses of nitrogen topdressing (0, 40, 80, 120 and 160 kg ha(-1)), using urea as nitrogen source. It was determined the dry mass of residue present as ground cover, the full flowering time, the leaf nitrogen content, the 100 grains mass, the grain yield, the processing income, the chemical soil properties and economic analysis of common bean grain yield. It was found the common bean grain productivity in succession to corn-grain was positively influenced by nitrogen fertilization, showing it is economically viable only when given 160 kg ha(-1) of nitrogen and the intercropping corn-grain and B. ruziziensis use is the best option when the common bean is sown in succession.
Nitrogen topdressing on common bean cropped in winter-spring in three cropping systems
Keywords: Phaseolus vulgaris; Brachiaria ruziziensis; Zea mays L.; no-tillage system